2017
DOI: 10.3390/nu9020142
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Intakes in 553 Dutch Elite and Sub-Elite Athletes: Prevalence of Low and High Intakes in Users and Non-Users of Nutritional Supplements

Abstract: This study investigated whether athletes meet micronutrient recommendations and whether the adequacy of their intake is related to the use of dietary supplements, sport nutrition products or a combination. Micronutrient intakes of 553 Dutch (sub-) elite athletes were assessed using web-based 24-h dietary recalls with accompanying nutritional supplement questionnaires. In the majority of both users and non-users of dietary supplements, vitamin D intake was below the estimated average requirement (AR) if supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 42 publications
8
55
2
6
Order By: Relevance
“…The usual intake of antioxidant-rich foods among athletes has shown to be significantly lower than the 5 portions a day recommended by national health authorities. 44 Thus, we are confident that the food-based antioxidant dose in our protocol produced a large enough increase compared to the subjects' usual intake. Furthermore, only one study subject reported discomfort with the intervention, indicating that it was welltolerated overall and feasible in the field setting.…”
Section: Discussionmentioning
confidence: 72%
“…The usual intake of antioxidant-rich foods among athletes has shown to be significantly lower than the 5 portions a day recommended by national health authorities. 44 Thus, we are confident that the food-based antioxidant dose in our protocol produced a large enough increase compared to the subjects' usual intake. Furthermore, only one study subject reported discomfort with the intervention, indicating that it was welltolerated overall and feasible in the field setting.…”
Section: Discussionmentioning
confidence: 72%
“…The Dutch athletes reported a lower intake of micronutrients, such as iron; vitamin D; vitamin B1 and B2; vitamin A, B3, and C; and selenium [10]. Recently, Marius et al [15] reported inadequate carbohydrate intakes in 80% of Lithuanian athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Retinol intakes above the UL among children have been reported in the United States 34,35,37 and Canada, 36 with prevalences ranging from 0% to 4% among children 4-8 years of age 34 to 59% among children 24-47 months of age. 35 Among adults, retinol intakes exceeding the UL were uncommon in the United States, Mexico, and several European countries, [49][50][51][52][53][54][55] but there was some evidence of excessive intake among supplement users. 51,52 In addition, fortified sugar has been implicated in reports of high VA intake and status in Guatemala, 56,57 Nicaragua, 58 and Zambia, 59,60 although, to our knowledge, national estimates of the prevalence of excessive intake or status are unavailable.…”
Section: Burden Of Excessive Intakesmentioning
confidence: 99%
“…35 Among adults, retinol intakes exceeding the UL were uncommon in the United States, Mexico, and several European countries, [49][50][51][52][53][54][55] but there was some evidence of excessive intake among supplement users. 51,52 In addition, fortified sugar has been implicated in reports of high VA intake and status in Guatemala, 56,57 Nicaragua, 58 and Zambia, 59,60 although, to our knowledge, national estimates of the prevalence of excessive intake or status are unavailable. children, 34,35,61 particularly in association with consumption of voluntarily fortified food, such as fortified breakfast cereal: 5-7% of children 1-8 years old in the highest quintile of fortified food intake had folic acid intake above the UL.…”
Section: Burden Of Excessive Intakesmentioning
confidence: 99%